1. The problem statement, all variables and given/known data I am told to find dy/dx by implicit differentiation where: e^(x^2 * y) = x + y 2. Relevant equations The above equation and the ln of it. 3. The attempt at a solution e^(x^2 * y) = x + y (x^2 * y)ln(e) = ln(x+y) x^2 * y = ln(x+y) x^2(dy/dx) + y(2x) = 1/(x+y) * (1 + dy/dx) (dy/dx)[x^2 - 1/(x+y)] = 1/(x+y) - 2xy dy/dx = (1/(x+y) - 2xy)/(x^2 - 1/(x+y)) or here: https://postimg.org/image/3k5ygbkxt/ This was marked wrong (online software). It doesn't care about simplest form and it was entered properly. So, what did I do wrong?